The Impact of Addiction to Gambling on the Capacity of Citizens - SHTYKOV, Viktor Pavlovich; SHTYKOVA, Ekaterina Ruslanovna; NOSENKO, Lidia Ivanovna; BONDARENKO, Natalia Grigorievna; FURSOV, Vladimir Alekseevich (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The work analyzes the current legislation on the limitation of legal capacity of citizens in connection with addiction to gambling. It is mentioned that the problem of addiction to gambling has existed both in Russia and in the world for many centuries, and technological progress has only aggravated this problem, which is still relevant for the Russian Federation. The legislator takes various measures aimed at solving the problem related to the addiction of citizens to gambling. It is indicated that not all changes made to the legislation of the Russian Federation had the necessary effect. The article justifies the position on the need to change both the legislative and law enforcement approach to the limitation of legal capacity for addiction to gambling.